PENDEKATAN THEORY OF PLANNED BEHAVIOR DALAM MELAKUKAN SERTIFIKASI HALAL BAGI PELAKU UMKM SEKTOR HALAL FOOD DI KABUPATEN BANGKALAN - Amaliatus Sholihah; Firman Setiawan (Politeknik Negeri Ambon, 2022)
ABSTRACT The Law on Halal Product Guarantee as stipulated in Law Number 33 of 2014 was officially passed on October 17, 2019. This has changed the nature of halal certification which was originally voluntary for business actors to become mandatory. However, in reality, until now in Indonesia, especially in Bangkalan Regency, there are still many MSME actors who have not implemented halal certification. There are several reasons that make MSME players reluctant to apply for halal certification, including the assumption that obtaining halal certification is a waste of time, money and effort, besides that they also think that applying for halal certification requires a fairly long process. In fact, this Halal certificate should be part of the responsibilities and duties of MSME actors to ensure product safety through a system set up by the Halal Product Guarantee Agency (BPJPH). Based on these problems, this study aims to determine the sentiment of MSME actors in carrying out halal certification. . Therefore, understanding what they think, what they do, as well as the perceived social influence, is very important to identify interest in a particular thing. Like the interest to do halal certification. This research is descriptive qualitative through phenomenological analysis. The data collection process will be carried out by conducting interviews and observation methods. Furthermore, it will be studied and explained clearly so that a conclusion is obtained to provide an overview of the actual situation of the research object which will then be published by an accredited journal so that it can be used as a new reading or reference.